Break Through the Limitation of Malus' Law with Plasmonic Polarizers. Issue 8 (15th May 2014) - Huang, Cheng‐ping; Wang, Qian‐jin; Yin, Xiao‐gang; Zhang, Yong; Li, Jia‐qi; Zhu, Yong‐yuan
<x xml:space="preserve">Abstract</x> Conventionally, light cannot pass through a pair of orthogonal linear polarizers. This limitation set by the law of Malus may be removed plasmonically. With a pair of specially designed orthogonal plasmonic polarizers, both high transmission and 90‐degree polarization conversion are suggested. The experimental demonstration of such an effect is also presented in both optical and microwave regimes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>